2013
DOI: 10.7243/2054-0841-1-2
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of screening services for cancer of the cervix in Makurdi, Nigeria

Abstract: Background: Cancer of the cervix is a leading cause of death due to female genital malignancies in developing countries. Early detection through cervical screening is crucial for prevention and treatment. Objective: To determine the awareness and utilization of screening services for cancer of the cervix amongst women in Makurdi. Methods: A cross-sectional study using interviewer administered questionnaires to women attending the outpatient gynecological clinic at the Benue State University Teaching Hospital, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…Lack of knowledge and awareness of cervical screening was cited as the most common barrier (Abotchie & Shokar, ; De Abreu, Horsfall, & Learmonth, ; Ebu, Mupepi, Siakwa, & Sampselle, ; Eze, Umeora, Obuna, Egwuatu, & Ejikeme, ; Lyimo & Beran, ; McFarland, ; Mosavel, Simon, Oakar, & Meyer, 2009; Mupepi, Sampselle, & Johnson, ; Terefe & Gaym, ; Utoo, Ngwan, & Anzaku, ; Were, Nyaberi, & Buziba, . Some women also reported lack of knowledge about cervical cancer as barriers to cervical cancer screening (Eze et al., ; Lyimo & Beran, ; Mupepi et al., ; Utoo et al., ). Other studies reported not knowing where to go for the Pap smear (Abotchie & Shokar, ; Ebu et al., ; Terefe & Gaym, ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Lack of knowledge and awareness of cervical screening was cited as the most common barrier (Abotchie & Shokar, ; De Abreu, Horsfall, & Learmonth, ; Ebu, Mupepi, Siakwa, & Sampselle, ; Eze, Umeora, Obuna, Egwuatu, & Ejikeme, ; Lyimo & Beran, ; McFarland, ; Mosavel, Simon, Oakar, & Meyer, 2009; Mupepi, Sampselle, & Johnson, ; Terefe & Gaym, ; Utoo, Ngwan, & Anzaku, ; Were, Nyaberi, & Buziba, . Some women also reported lack of knowledge about cervical cancer as barriers to cervical cancer screening (Eze et al., ; Lyimo & Beran, ; Mupepi et al., ; Utoo et al., ). Other studies reported not knowing where to go for the Pap smear (Abotchie & Shokar, ; Ebu et al., ; Terefe & Gaym, ).…”
Section: Resultsmentioning
confidence: 99%
“…Other beliefs included not perceiving Pap smear as beneficial, because cervical cancer cannot be prevented (Mosavel, 2009). The following attitudes were also reported: cervical screening not viewed as important or necessary (Adetola, ; Eze et al., ; Fort et al., ; McFarland, ; Terefe & Gaym, ; Utoo et al., ) and the embarrassment of the test (Ebu et al., ; Lyimo & Beran, ; Mosavel, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations